Illustrated guide to Pentatominae (Hemiptera: Pentatomidae) species associated with the four main grain crops in Rio Grande do Sul state, Brazil - Barros, Lurdiana D.; Paim, Marcelo R.; Krein, Verônica; Carabajal, Victor; Brandão, Marcela N.; Bernardes, Paula De O.; Lindner, Mariana F. (Zootaxa, 2021)
Several stink bugs in the subfamily Pentatominae are crop pests or have the potential to damage plants of economic importance. In the Brazilian state of Rio Grande do Sul, where agriculture plays a major role in the economy, the knowledge about pest stink bugs is fragmented and, in some instances, outdated. This work provides a summary of Pentatominae species recorded in Rio Grande do Sul feeding on the four most important grain crops for the state, i.e. soybean, rice, maize, and wheat, plus canola, an emerging crop. This survey is enhanced with new records from scientific collections, a short diagnosis for each species, distribution maps, an identification key, and carefully illustrated to allow for species recognition in the field. With this work, we aim to reunite the scattered knowledge of the group in one single revision, and provide a useful tool for identifying the pest stink bugs of Rio Grande do Sul.